Employee job satisfaction of Dhaka Bank Limited’s local export team, Corporate Branch - Hossain, AKM Mahim (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.